2017
DOI: 10.1021/acsnano.7b03321
|View full text |Cite
|
Sign up to set email alerts
|

ZnS-Sb2S3@C Core-Double Shell Polyhedron Structure Derived from Metal–Organic Framework as Anodes for High Performance Sodium Ion Batteries

Abstract: Taking advantage of zeolitic imidazolate framework (ZIF-8), ZnS-SbS@C core-double shell polyhedron structure is synthesized through a sulfurization reaction between Zn dissociated from ZIF-8 and S from thioacetamide (TAA), and subsequently a metal cation exchange process between Zn and Sb, in which carbon layer is introduced from polymeric resorcinol-formaldehyde to prevent the collapse of the polyhedron. The polyhedron composite with a ZnS inner-core and SbS/C double-shell as anode for sodium ion batteries (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
182
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(188 citation statements)
references
References 52 publications
5
182
0
1
Order By: Relevance
“…In addition, the biphasic material may contribute to high electronic conductivity and pseudocapacitive effect, leading to the fast ion diffusion kinetics. Moreover, the biphasic material with stepwise redox reactions can effectively reduce the solid‐state diffusion and thus relieve the stress during the insertion of ions . Remarkably, many zinc vanadates were demonstrated to exhibit superior electrochemical behavior as aqueous ZIB cathodes, especially the Zn 0.25 V 2 O 5 · n H 2 O material reported by Nazar and co‐workers, whose study revealed that Zn 0.25 V 2 O 5 · n H 2 O can perform at a high capacity and demonstrate excellent long‐term cyclic stability in virtue of its favorable structure.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the biphasic material may contribute to high electronic conductivity and pseudocapacitive effect, leading to the fast ion diffusion kinetics. Moreover, the biphasic material with stepwise redox reactions can effectively reduce the solid‐state diffusion and thus relieve the stress during the insertion of ions . Remarkably, many zinc vanadates were demonstrated to exhibit superior electrochemical behavior as aqueous ZIB cathodes, especially the Zn 0.25 V 2 O 5 · n H 2 O material reported by Nazar and co‐workers, whose study revealed that Zn 0.25 V 2 O 5 · n H 2 O can perform at a high capacity and demonstrate excellent long‐term cyclic stability in virtue of its favorable structure.…”
Section: Resultsmentioning
confidence: 99%
“…From in Figure a, the Raman spectroscopy of the Sn@Sb 2 S 3 ‐rGO composite exhibits the two characteristic Raman shift at 1330 and 1590 cm −1 consistent with the disordered carbon (D band) and ordered graphitic carbon (G band), which declares the superior reductive degree of the rGO. The obvious peak at 280 cm −1 lying in Raman spectroscopy can be ascribed to Sb 2 S 3 . Based on the thermogravimetric analysis (TGA) result, the carbon content is about 12.4 % (Figure b).…”
Section: Resultsmentioning
confidence: 96%
“…a) Schematic for the fabrication process and b) TEM images of ZnS‐Sb 2 S 3 @C core–shell polyhedrons. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Mof Composites With Polymeric Materialsmentioning
confidence: 99%
“…The introduction of polymers on the surface of MOFs can also act as a stabilization layer for the derivatives. Recently, a resorcinol‐formaldehyde (RF) was engineered on the surface of Zif‐8 by Yin and co‐workers to stabilize the polyhedron structure so as to obtain a robust composite to endure the subsequent sulfurization process (Figure a,b) . After the sulfidation with TAA and the cation exchange process with Sb 3+ , a core–double shell ZnS‐Sb 2 S 3 @C structure was finally obtained, which exhibited a high reversible capacity of 630 mAh g −1 after 120 cycles with a high columbic efficiency of nearly 100% when tested as anode materials for sodium‐ion batteries.…”
Section: Mof Composites With Polymeric Materialsmentioning
confidence: 99%